2log(x)-log(3)=1

Simple and best practice solution for 2log(x)-log(3)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2log(x)-log(3)=1 equation:


Simplifying
2log(x) + -1log(3) = 1

Multiply glo * x
2glox + -1log(3) = 1

Reorder the terms for easier multiplication:
2glox + -1 * 3glo = 1

Multiply -1 * 3
2glox + -3glo = 1

Reorder the terms:
-3glo + 2glox = 1

Solving
-3glo + 2glox = 1

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Reorder the terms:
-1 + -3glo + 2glox = 1 + -1

Combine like terms: 1 + -1 = 0
-1 + -3glo + 2glox = 0

The solution to this equation could not be determined.

See similar equations:

| 3x-24+2x+1=180 | | 8+5y=-17 | | g+9=15 | | 36s^2-4t^2= | | 4c^2-12ct+9t^2= | | x-40=4x+5 | | 6(m+3)-2m=38 | | r-4=8 | | -5/3x=-15 | | 1-m^6= | | 4x=(3x+40) | | 6+4a-1+6a= | | 110-32= | | 6.21y+3-4.5y+1.45=3.5y | | 3(-1+3y)+3=3y | | -13x=x^2 | | 1+s=10 | | 4(n-3)+6=4n-3 | | 50+2x+2x+20=180 | | 8+n=17 | | 3+d=17 | | 8(x-4)=75 | | 7(c-12)=-2 | | 1/3=5 | | 2-7.5s=28 | | 9+m=99 | | 6(3x-1)=84 | | n+2=-14-x | | 29+12x=21+12x | | 9+q=14 | | 49b^2-112bp+64p^2= | | 2(x-6)+8=14 |

Equations solver categories